Method for electrochemical synthesis of urea

By designing an iron-based catalyst containing asymmetric oxygen vacancies, the problem of insufficient CO2 activation ability in electrocatalytic synthesis of urea is solved, efficient urea generation and stability are achieved, and the potential for industrial development is achieved.

CN119162589AActive Publication Date: 2024-12-20INST OF CHEM CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411299725.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

During the electrocatalytic synthesis of urea, the activation ability of CO2 is insufficient, which makes it difficult to achieve high yield and high selectivity of urea, and the occurrence of side reactions affects the performance of the catalyst.

Method used

An iron-based catalyst containing asymmetric oxygen vacancies was designed, prepared by hydrothermal method and ultrasonic dispersion technology, combined with hydrogen and argon high-temperature calcination, forming a catalyst with polarized adsorption molecules, and combined with carbon fiber paper for electrochemistry. Reduction reaction of CO2 and nitrate in the catalytic system.

Benefits of technology

The urea generation rate and selectivity have been significantly improved, the Faraday efficiency has reached 63%, and the catalyst has good stability during long-term operation and has the potential for industrial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162589A_ABST
    Figure CN119162589A_ABST
Patent Text Reader

Abstract

The invention provides a method for electrochemical synthesis of urea. According to the invention, a metal-doped catalyst with an asymmetric oxygen vacancy structure is designed and prepared, and CO2 and nitrate are catalytically converted into urea by using the catalyst as an electrode material and CO2 and nitrate as raw materials in an H-type electrolytic tank by using an electrochemical means. The Faraday efficiency of the obtained main product urea reaches 63%, and the generation rate of the urea reaches 7.5 g / h <-1 > gcat <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemistry and chemical engineering, and specifically relates to a method for synthesizing urea by electrochemically catalyzing the conversion of carbon dioxide and nitrate. Background Art

[0002] With the increasing severity of global warming and environmental pollution, carbon dioxide (CO2) emissions have become a global problem that needs to be solved urgently. The electrocatalytic conversion of carbon dioxide into valuable chemicals not only helps to store renewable energy, but also can alleviate the burden of anthropogenic carbon cycles to a certain extent, providing a promising solution. Urea, as an important bulk chemical, is widely used in the production of agricultural fertilizers. The optimization of its synthesis process is of great significance to improving resource utilization efficiency and reducing environmental pollution. In the field of electrocatalytic conversion, coupling CO2 with nitrates to form urea broadens the reaction path of electrocatalytic conversion of CO2, provides a new way to achieve efficient urea synthesis, and plays a positive role in the realization of green chemistry and circular economy.

[0003] However, there are many challenges in the electrocatalytic synthesis of urea. First, the synthesis of urea involves complex issues such as co-activation of multiple reactants, multi-step proton-coupled electron transfer, and competitive hydrogenation of intermediates. In particular, there is a mismatch in rate and kinetics in the electroreduction reaction of nitrate and CO2, and the reactivity of nitrate on the catalyst is generally stronger than that of CO2. Therefore, catalyst design needs to focus on improving the activation ability of CO2 to achieve high yield and high selectivity for urea. Secondly, during the urea generation process, CO2 or nitrate is easily over-reduced, leading to the occurrence of side reactions. For example, during the nitrate reduction process, ammonia may be produced. This byproduct not only affects the selectivity of urea, but may also cause the performance of the catalyst to deteriorate. In order to cope with these problems, catalyst design needs to have the ability to promote the effective activation of CO2 and inhibit the generation of by-products.

[0004] Defect engineering is an effective electrocatalyst design technique that is widely used to improve the electronic structure and surface properties of electrodes. Among them, oxygen vacancies have attracted extensive attention due to their ability to regulate reaction sites and accelerate electron transfer. However, due to the high cation symmetry, the electron distribution in oxygen vacancies is usually relatively uniform, which limits their catalytic activity. Summary of the invention

[0005] One of the purposes of the present invention is to provide an iron-based catalyst containing asymmetric oxygen vacancies and a preparation method thereof.

[0006] The iron-based catalyst containing asymmetric oxygen vacancies provided by the present invention is prepared by a method comprising the following steps:

[0007] 1) dissolving the iron compound in a solvent, stirring to obtain a mixed solution, adding acetate and continuing to stir, heating in a hydrothermal autoclave to react, and obtaining a Fe2O3 catalyst;

[0008] 2) dissolving the Fe2O3 catalyst in a solvent, performing ultrasonic dispersion, adding a doped metal compound, heating and stirring in a water bath, and obtaining a metal-doped Fe2O3 catalyst;

[0009] 3) The obtained metal-doped Fe2O3 catalyst is calcined at high temperature in a hydrogen-argon mixed atmosphere to obtain an iron-based catalyst containing asymmetric oxygen vacancies.

[0010] In step 1) of the above method, the iron compound is selected from at least one of ferric chloride (FeCl3), ferric sulfate (Fe2(SO4)3), ferric nitrate (Fe(NO3)3) and hydrates thereof, specifically FeCl3 hydrate, more specifically FeCl3·6H2O;

[0011] The solvent is selected from at least one of ethanol, ethylene glycol, acetone, acetonitrile, tetrahydrofuran, and N,N-dimethylformamide;

[0012] The acetate may be selected from at least one of sodium acetate, potassium acetate, ammonium acetate and hydrates thereof;

[0013] The molar ratio of iron ions to acetate in the iron compound may be 1:1-100, specifically 1:1-20, more specifically 1:10;

[0014] The dissolution is carried out by magnetic stirring, and the stirring speed can be 300-800 r min -1 , specifically 600r min -1 ;

[0015] The hydrothermal reactor heating reaction temperature can be 0-280°C, specifically 180°C, and the time can be 6-72h, specifically 24h;

[0016] The above method step 1) further comprises the operation of centrifuging the reaction system, collecting the precipitate, washing and drying to obtain the Fe2O3 catalyst after the reaction is completed;

[0017] Wherein, the centrifugal speed may be 4000-10000 rpm, and the time may be 1-60 min, specifically 6000 rpm, 5 min;

[0018] The washing solvent may be at least one of deionized water, ethanol, acetone and methanol;

[0019] The drying temperature may be 30-100° C., and the drying time may be 1-50 hours, and specifically may be 60° C. for 12 hours.

[0020] In step 2) of the above method, the solvent is selected from at least one of ethanol, ethylene glycol, acetone, acetonitrile, tetrahydrofuran, and N,N-dimethylformamide;

[0021] The ultrasonic dispersion time may be 0-10 hours, specifically 1 hour;

[0022] The doping metal compound is selected from at least one of a transition metal compound, an alkaline earth metal compound, and a lanthanide metal compound;

[0023] Specifically, it can be at least one of transition metal nitrates, transition metal chlorides, alkaline earth metal nitrates, alkaline earth metal chlorides, lanthanide metal nitrates, lanthanide metal chlorides and hydrates thereof, including at least one of zinc nitrate (Zn(NO3)2), zinc chloride (ZnCl2), indium nitrate (In(NO3)3), indium chloride (InCl3), cerium nitrate (Ce(NO3)3), cerium chloride (CeCl3) and hydrates thereof, more specifically Zn(NO3)2·6H2O;

[0024] The feed mass ratio of the doped metal compound to the Fe2O3 catalyst may be 0.01-10:10, specifically 1-3:10; more specifically 2-3:10;

[0025] The water bath heating temperature is 0-100°C, specifically 70°C;

[0026] The water bath stirring speed can be 300-800 r min -1 , specifically 600r min -1 ;

[0027] The water bath heating and stirring time may be 1-24 hours, specifically 8 hours.

[0028] Step 2) of the above method also includes the operations of centrifuging the reaction system, collecting the precipitate, washing, and drying to obtain the metal-doped Fe2O3 catalyst;

[0029] Wherein, the centrifugal speed may be 4000-10000 rpm, and the time may be 1-60 min, specifically 5000 rpm, 5 min;

[0030] The washing solvent may be at least one of deionized water, ethanol, acetone and methanol; the drying temperature may be 30-100° C., and the drying time may be 1-50 hours, specifically, drying at 60° C. for 12 hours.

[0031] In step 3) of the above method, the volume ratio of H2 to Ar in the hydrogen-argon mixed atmosphere is 1:9;

[0032] The temperature of the high temperature calcination may be 50-800°C, specifically 200°C, wherein the heating rate is 1-20°C / min, specifically 2°C / min;

[0033] The high temperature calcination time may be 1-20 hours, specifically 4 hours.

[0034] The second object of the present invention is to provide an electrode material.

[0035] The electrode material provided by the present invention comprises the above-mentioned iron-based catalyst containing asymmetric oxygen vacancies.

[0036] The electrode material also includes carbon fiber paper.

[0037] The electrode material is prepared by a method comprising the following steps:

[0038] The iron-based catalyst containing asymmetric oxygen vacancies is dispersed in an organic solvent, and Nafion D-520 dispersion is added as a binder to obtain a dispersion; the dispersion is drop-coated on the carbon fiber paper to obtain the electrode material.

[0039] In the method, the organic solvent is selected from at least one of acetone, ethanol, isopropanol and methanol;

[0040] The ratio of the Nafion D-520 dispersion to the iron-based catalyst containing asymmetric oxygen vacancies may be 1-20 μL:1 mg, specifically 10 μL:1 mg;

[0041] On the carbon fiber paper layer, the amount of the catalyst can be 0.01 to 10 mg cm -2 , specifically 0.1 mg cm -2 .

[0042] The third object of the present invention is to provide an electrochemical catalytic system for preparing urea by reducing CO2 and nitrate.

[0043] The electrochemical catalytic system for preparing urea by reducing CO2 and nitrate provided by the present invention comprises the above-mentioned electrode material, reaction electrolyte and reaction device;

[0044] The reaction electrolyte is selected from at least one of the following: KNO3 aqueous solution, KHCO3+KNO3 aqueous solution, KNO2 aqueous solution, KNO2+KHCO3 aqueous solution, NaNO3 aqueous solution, NaNO3+NaHCO3 aqueous solution, NaNO2 aqueous solution, NaNO2+NaHCO3 aqueous solution;

[0045] The concentration of the reaction electrolyte may be 0.01-10M;

[0046] Preferably 0.2M KHCO3+0.1M KNO3 aqueous solution;

[0047] The reaction device may be a flow-type electrolytic cell or an H-type electrolytic cell, preferably an H-type electrolytic cell.

[0048] The application of the above-mentioned iron-based catalysts, electrode materials, and electrochemical catalytic systems containing asymmetric oxygen vacancies in the electrochemical catalytic conversion of CO2 and nitrate reduction to synthesize urea also falls within the protection scope of the present invention.

[0049] The present invention also provides a method for synthesizing urea by electrochemical catalytic conversion of CO2 and nitrate.

[0050] The method for synthesizing urea by electrochemical catalytic conversion of CO2 and nitrate provided by the present invention comprises the following steps: using the above-mentioned electrochemical catalytic system, taking CO2 and nitrate as raw materials, and performing a constant potential electrolysis reaction in an electrolytic cell reaction device through the action of electrode materials and electrolyte to obtain urea.

[0051] In the above method, the reaction potential in the H-type electrolytic cell system can be -0.1 to -1.4 V versus RHE, preferably -0.7 V; the reaction time can be 0.1-100 hours, preferably 0.1-10 hours; and the main product of the reaction is urea.

[0052] The present invention designs and prepares a metal-doped catalyst with an asymmetric oxygen vacancy structure. The asymmetric oxygen vacancy can make the adsorbed molecules more polarized, reduce the adsorption energy barrier, promote the co-activation of CO2 and nitrate and the coupling of carbon-nitrogen bonds, and significantly improve the activity of electrocatalytic synthesis of urea.

[0053] The present invention proposes to use CO2 and nitrate as raw materials and use electrochemical means to catalyze the conversion of CO2 and nitrate into urea. The reaction can be carried out efficiently in an H-type electrolytic cell using Fe2O3 catalyst containing asymmetric oxygen vacancies as electrode material. The Faradaic efficiency of the main product urea can reach 63%, and the urea generation rate can reach 7.5gh. -1 g cat -1 . In addition, the catalyst of the present invention has good stability under long-term operation conditions and has the potential for industrial application. The method adopts a simple and scalable synthesis route to improve the efficiency of large-scale reuse of CO2 and nitrate resources. The catalyst of the present invention has an excellent urea production rate, laying a solid foundation for its industrial development, and is of far-reaching significance in solving energy crises and environmental problems. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 20% Zn-Fe2O3 / O prepared in Example 1 of the present invention V Scanning electron microscope (SEM) images of

[0055] Figure 2 20% Zn-Fe2O3 / O prepared in Example 1 of the present invention V X-ray diffraction analysis (XRD) pattern;

[0056] Figure 3 20% Zn-Fe2O3 / O prepared in Example 1 of the present invention V Element distribution map (EDS Mapping);

[0057] Figure 4 For different Zn content Fe2O3 / O V Electrochemical reduction of CO2 and NO3 - is the Faraday efficiency diagram of urea;

[0058] Figure 5 20% Zn-Fe2O3 / O V Electrochemical reduction of CO2 and NO3 - is the Faraday efficiency diagram of urea;

[0059] Figure 6 20% Zn-Fe2O3 / O V urea production rate diagram. DETAILED DESCRIPTION

[0060] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0061] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0062] Example 1. Preparation and characterization of catalyst

[0063] Zn-O containing asymmetric oxygen vacancies V -Fe structured Zn-doped iron oxide (Zn-Fe2O3 / O V ) catalyst preparation as an example.

[0064] First, 5 mmol of FeCl3·6H2O and 2.8 mL of H2O were magnetically stirred (600 r min -1) was dissolved in 40 mL of ethanol solution until it was completely dissolved. Then 50 mmol CH3COONa was added to the above solution and stirring was continued for 30 minutes. The obtained mixed solution was placed in a 100 mL hydrothermal kettle, and then the hydrothermal kettle was placed in an oven and kept at 180°C for 24 hours. After cooling naturally to room temperature, centrifugation was performed at 6000 rpm for 5 minutes to obtain a precipitate. After washing with deionized water and ethanol respectively, the obtained precipitate was placed in a vacuum drying oven at 60°C for 12 hours to obtain a Fe2O3 catalyst.

[0065] Then, 50 mg of the prepared Fe2O3 catalyst was dissolved in 50 ml of ethanol and ultrasonicated for 1 h to make the solution uniformly dispersed. 500, 1000, and 1500 μL of 10 mg mL -1 The mixture was stirred continuously (600 r min) in a 70 °C water bath. -1 ) for 8 hours, the reaction system was centrifuged, the precipitate was collected, the mixture was washed with deionized water and ethanol, and dried in a vacuum drying oven at 60°C for 12 hours. Finally, the prepared Zn-Fe2O3 was placed in a tube furnace, H2 / Ar (10% / 90%, v / v) mixed gas was introduced, and heated at 200°C (heating rate of 2°C / min) for 4 hours to obtain Zn-Fe2O3 / O with a feed mass ratio of Zn(NO3)2 and Fe2O3 of 10%, 20%, and 30%. V Catalysts, named 10% Zn-Fe2O3 / O V , 20% Zn-Fe2O3 / O V , 30% Zn-Fe2O3 / O V .

[0066] Based on the above method, Mn-Fe2O3 / O2 containing asymmetric oxygen vacancy structure was prepared using Mn(NO3)2, Co(NO3)2, Ni(NO3)2, Pd(NO3)2, Cu(NO3)2, Al(NO3)3, Ga(NO3)3, In(NO3)3, Sn(NO3)4, Pb(NO3)2, Ce(NO3)3, and Ti(CH3CH2O)4. V 、Co-Fe2O3 / O V 、Ni-Fe2O3 / O V 、Pd-Fe2O3 / O V 、Cu-Fe2O3 / O V 、Al-Fe2O3 / O V 、Ga-Fe2O3 / O V 、In-Fe2O3 / O V 、Sn-Fe2O3 / O V、Pb-Fe2O3 / O V 、Ce-Fe2O3 / O V 、Ti-Fe2O3 / O V catalyst.

[0067] For comparison, the prepared Fe2O3 catalyst was placed in a tubular furnace, and a H2 / Ar (10% / 90%, v / v) mixed gas was introduced and heated at 200°C for 4 hours to synthesize Fe2O3 / O V catalyst.

[0068] For 20% Zn-Fe2O3 / O V The catalyst was systematically characterized. Scanning electron microscope (SEM) images showed that the synthesized 20% Zn-Fe2O3 / O V With hexagonal nanosheet morphology ( Figure 1 ). X-ray diffraction analysis (XRD) showed that Zn-Fe2O3 / O V The catalyst phase structure is iron oxide ( Figure 2 ). The EDS Mapping study showed that Zn, Fe, and O elements were evenly distributed on the catalyst surface ( Figure 3 ).

[0069] The catalyst prepared above: Mn-Fe2O3 / O V 、Co-Fe2O3 / O V 、Ni-Fe2O3 / O V 、Pd-Fe2O3 / O V 、Cu-Fe2O3 / O V 、Al-Fe2O3 / O V 、Ga-Fe2O3 / O V 、In-Fe2O3 / O V 、Sn-Fe2O3 / O V 、Pb-Fe2O3 / O V 、Ce-Fe2O3 / O V 、Ti-Fe2O3 / O V The structure of Zn-Fe2O3 / O V The catalysts are similar.

[0070] The Fe2O3 / O prepared above V Catalyst structure and Zn-Fe2O3 / O V The catalysts are similar, but only Fe and O elements are evenly distributed on the catalyst surface.

[0071] Example 2: Electrocatalytic synthesis of urea

[0072] Preparation of working electrode: First, 1 mg Zn-Fe2O3 / OV The catalyst (prepared in Example 1 of the present invention) was dispersed in 1 mL of isopropanol together with 10 μL of Nafion D-520 dispersion (5 wt%) and ultrasonicated for 1 h to make it uniformly dispersed. The dispersion was evenly drop-coated on the surface of the carbon fiber paper and dried at room temperature to form a thin catalyst layer. The catalyst loading on each electrode was 0.1 mg cm -2 .

[0073] All electrochemical experiments were completed on an electrochemical workstation (CHI 660E, Shanghai Chenhua Instrument Co., Ltd.). The electrolysis experiment was carried out at 25°C. The electrolytic cell device used was a three-electrode H-type electrolytic cell system. The three electrodes included the above-mentioned working electrode, a platinum counter electrode, and an Ag / AgCl reference electrode. Nafion 117 membrane was used as a proton exchange membrane to separate the cathode and the anode. The cathode chamber and the anode chamber were both filled with 0.2M KHCO3+0.1M KNO3 aqueous solution as the electrolyte, and the electrolyte dosage was 30mL. Before the electrochemical test, the cathode electrolyte was purged with CO2 at a flow rate of 30mL / min for 30min, and a constant CO2 flow rate was maintained during the test. The voltage range was -0.5 to -0.9V versus RHE, and the electrolysis time was 0.5h.

[0074] Product analysis: The gaseous products were collected by gas bags and analyzed by gas chromatography (GC, HP 4890D). Urea was analyzed by urease decomposition method and nuclear magnetic resonance (NMR). 1 H NMR, Bruker Avance III 400HD) was used for analysis, and other liquid products were detected by UV-visible spectrophotometer.

[0075] Electrocatalysis of CO2 and NO3 by catalysts with different Zn doping contents - The test results of the reaction are as follows Figure 4 As shown, 20% Zn-Fe2O3 / O V Electrocatalytic CO2 and NO3 under different catalytic conditions - The test results of the reaction are as follows Figure 5 , Figure 6 As can be seen from the figure, the catalytic system of the present invention can achieve excellent selectivity for urea (Faraday efficiency greater than 60%) and high urea production rate (close to 7.5gh -1 g cat -1 ).

[0076] Example 3: Study on catalyst stability

[0077] Ten cycles of stability testing were performed at -0.7 V versus RHE to evaluate the performance of 20% Zn-Fe2O3 / O VIt was found that the Faradaic efficiency of urea and the urea production rate did not change significantly (the results are shown in Table 1), indicating that the catalyst has excellent electrochemical stability and potential industrial value.

[0078] Table 1 Zn-Fe2O3 / O V Variation of urea Faraday efficiency and generation rate with cycle number in stability test

[0079] Cyclic stability test times Urea Faraday efficiency (%) <![CDATA[Urea production rate (g h -1 g cat -1 )]]> 1 63.3 5.67 2 61.5 5.37 3 62.8 5.41 4 60.1 5.22 5 61.9 5.28 6 61.1 5.30 7 63.2 5.52 8 62.5 5.42 9 61.4 5.30 10 61.6 5.23

[0080] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, and without the need to carry out unnecessary experimental conditions, the present invention can be implemented in a wide range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principles of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departure from the disclosed scope in the application, and changes made with conventional techniques known in the art.

Claims

1. An iron-based catalyst containing an asymmetric oxygen vacancy, prepared by a method comprising the following steps: 1) dissolving the iron compound in a solvent, stirring to obtain a mixed solution, adding acetate and continuing to stir, heating in a hydrothermal autoclave for reaction, and obtaining a Fe2O3 catalyst; 2) dissolving the Fe2O3 catalyst in a solvent, performing ultrasonic dispersion, adding a doped metal compound, heating and stirring in a water bath, and obtaining a metal-doped Fe2O3 catalyst; 3) The obtained metal-doped Fe2O3 catalyst is calcined at high temperature in a hydrogen-argon mixed atmosphere to obtain an iron-based catalyst containing asymmetric oxygen vacancies.

2. The iron-based catalyst according to claim 1, characterized in that In step 1), the iron compound is selected from at least one of ferric chloride, ferric sulfate, ferric nitrate and hydrates thereof; The acetate is selected from at least one of sodium acetate, potassium acetate, ammonium acetate and hydrates thereof; The molar ratio of iron ions to acetate in the iron compound is 1:1-100; The hydrothermal reactor is heated to a reaction temperature of 0-280° C. for a reaction time of 6-72 hours.

3. The iron-based catalyst according to claim 1, characterized in that In step 2), the doping metal compound is selected from at least one of a transition metal compound, an alkaline earth metal compound, and a lanthanide metal compound; The feed mass ratio of the doped metal compound to the Fe2O3 catalyst is 0.01-10:10; The water bath heating temperature is 0-100°C; The water bath stirring speed is 300-800 r / min -1 ; The time of heating and stirring in the water bath is 1-24h.

4. The iron-based catalyst according to claim 1, characterized in that In step 3), the volume ratio of H2 to Ar in the hydrogen-argon mixed atmosphere is 1:9; The high temperature calcination temperature is 50-800°C, wherein the heating rate is 1-20°C / min; The high temperature calcination time is 1-20h.

5. An electrode material, comprising the iron-based catalyst containing asymmetric oxygen vacancies according to any one of claims 1 to 4.

6. A method for preparing the electrode material according to claim 5, comprising the following steps: dispersing the iron-based catalyst containing asymmetric oxygen vacancies in an organic solvent, and adding Nafion D-520 dispersion as a binder to obtain a dispersion; drop-coating the dispersion onto the carbon fiber paper to obtain the electrode material; in, On the carbon fiber paper layer, the amount of the catalyst is 0.01 to 10 mg cm -2 .

7. An electrochemical catalytic system for preparing urea by reducing CO2 and nitrate, comprising the electrode material according to claim 5, a reaction electrolyte and a reaction device; in, The reaction electrolyte is selected from at least one of the following: KNO3 aqueous solution, KHCO3+KNO3 aqueous solution, KNO2 aqueous solution, KNO2+KHCO3 aqueous solution, NaNO3 aqueous solution, NaNO3+NaHCO3 aqueous solution, NaNO2 aqueous solution, NaNO2+NaHCO3 aqueous solution; The concentration of the reaction electrolyte is 0.01-10M; The reaction device is a flow-type electrolytic cell or an H-type electrolytic cell.

8. Use of the iron-based catalyst containing asymmetric oxygen vacancies according to any one of claims 1 to 4, the electrode material according to claim 5, or the electrochemical catalytic system according to claim 7 in electrochemical catalytic conversion of CO2 and nitrate reduction to synthesize urea.

9. A method for synthesizing urea by electrochemical catalytic conversion of CO2 and nitrate, comprising the following steps: using the electrochemical catalytic system described in claim 7, taking CO2 and nitrate as raw materials, and performing a constant potential electrolysis reaction in an electrolytic cell reaction device through the action of electrode materials and electrolyte to obtain urea.

10. The method according to claim 9, characterized in that The reaction potential in the electrolytic cell system is -0.1 to -1.4 V versus RHE; the reaction time is 0.1 to 100 hours.

Citation Information

Patent Citations

  • Preparation method of titanium-doped iron oxide photo-anode with high photoelectric water decomposition performance

    CN111364050A

  • Samarium-doped iron oxide SCR denitration catalyst as well as preparation method and application thereof

    CN112569952A

  • Copper-doped hematite (Cu-Fe2O3) photoelectrode film and preparation method and application thereof

    CN113019366A

  • Preparation method and application of oxygen vacancy-rich metal-doped hematite material

    CN116212881A

  • Ti / Fe2O3-Co-MOF composite photoelectrode and preparation and application thereof

    CN116716631A

Cited By

  • Preparation method and application of P-Cu / Fe2O3 bimetallic composite material

    CN119800405A